Relationship between participation in in-service training program and academic competencies among sports science university lecturers / Ali Ibrahim Ali Dawo - Ali Dawo, Ali Ibrahim (Institute of Graduate Studies, UiTM, 2015)
In-service training programs have emerged as an ideal training platform for lecturers in various universities to enhance their professional competencies. This becomes a necessity owing to the rapid advances that prompt the acquisition of knowledge to improve the lecturers’ competencies especially in sports science. The purpose of this study lies in investigating the relationship between participation in in-service training programs and academic competencies among Sport Science Lecturers in Libya and Malaysia. The need for in-service training among lecturers based on their participation in in-service activities was based on participation in planning (PPL), participation in implementation (PIM) and participation in evaluation (PEV). The competencies of Lecturers place focus on the competencies in planning instruction (CPI), competencies in conducting instruction (CCI), competencies evaluating instruction (CEI) and competencies in facilitating student’s growth (CFS). Previous studies were reviewed to support the arguments presented in this study using prominent theories such as the Perceptual Psychology Theory, Innovation Theory of planned behaviour (ITPB) and Contingency Theory. To achieve the objectives of this study, a quantitative study based on the survey questionnaire was used to collect primary data from 320 sports science lecturers within 11 Universities in Libya and Malaysia…